2008
DOI: 10.1152/ajpgi.90329.2008
|View full text |Cite
|
Sign up to set email alerts
|

Significance of ERK nitration in portal hypertensive gastropathy and its therapeutic implications

Abstract: tal hypertensive (PHT) gastric mucosa increases susceptibility to injury and delayed mucosal healing. It is possible that nitration of ERK by peroxynitrite might alter MAPK (ERK) signaling in PHT gastric mucosa, leading to delayed mucosal healing, since excessive nitric oxide production is implicated in PHT gastric mucosa and MAPK (ERK) signaling induces cell proliferation and leads to gastric mucosal healing in response to injury. Portal hypertension was produced by staged portal vein ligation, and sham-opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 44 publications
2
24
0
5
Order By: Relevance
“…These results were inconsistent with those of Hong et al (1998), who noted similar effects of rebamipide against liver damage induced by endotoxic shock. Further, the present results confirmed previously reported data from several studies that comment on the anti-oxidant activity imparted by rebamipide (Hahm et al 1997;Kinjo et al 2008;Tokuhara et al 2008).…”
Section: Discussionsupporting
confidence: 92%
“…These results were inconsistent with those of Hong et al (1998), who noted similar effects of rebamipide against liver damage induced by endotoxic shock. Further, the present results confirmed previously reported data from several studies that comment on the anti-oxidant activity imparted by rebamipide (Hahm et al 1997;Kinjo et al 2008;Tokuhara et al 2008).…”
Section: Discussionsupporting
confidence: 92%
“…Intragastric administration ameliorates oxidative stress, reduces nitration of tyrosine residues of ERK, and reverses delayed mucosal healing occurring in PHG. It reversed the increased susceptibility to ethanol-induced injury and reversed the delayed healing after gastric injury in rats with PHG [145] . Kinjo et al [145] reported that administration of rebamipide in rats with PHG, significantly decreased lipid peroxide and nitrotyrosine and nitration of ERK by peroxynitrite in PHG mucosa, therefore normalizing ERK activation and restoring normal gastric mucosal healing after ethanol injury.…”
Section: Vasopressin and Terlipressinmentioning
confidence: 86%
“…It reversed the increased susceptibility to ethanol-induced injury and reversed the delayed healing after gastric injury in rats with PHG [145] . Kinjo et al [145] reported that administration of rebamipide in rats with PHG, significantly decreased lipid peroxide and nitrotyrosine and nitration of ERK by peroxynitrite in PHG mucosa, therefore normalizing ERK activation and restoring normal gastric mucosal healing after ethanol injury. Rebamipide requires further study as a therapy for PHG [119] .…”
Section: Vasopressin and Terlipressinmentioning
confidence: 86%
See 1 more Smart Citation
“…Indeed, parietal cell loss and impaired acid secretion have been reported as consequences of portal hypertensive gastropathy (1,24). Moreover, in portal hypertensive gastric mucosa, tyrosine nitration has been reported as a result of peroxynitrite formation from elevated superoxide and nitric oxide production (26,37). Enzymes integral to mitochondrial oxidative phosphorylation (e.g., aconitase and ATP synthase), as well as SOD2 itself, have been demonstrated to be targets of inactivation by tyrosine nitration (13,14,35).…”
mentioning
confidence: 99%